Cultural group perception enhances sense of agency in a multicultural society. Issue 4 (23rd May 2019) - Li, Ming; Li, Liman Man Wai; Zhao, Ke; Gao, Ding‐Guo
Abstract : Group, which involves collective actions for achieving shared goals, can be conceptually understood as an important source of agency and control. The current research investigated whether group identity salience can enhance sense of agency within the individual. Specifically, we examined whether an activated cultural group identity, through presenting different types of cultural photographs in a predictable way, would facilitate people's sense of agency by using an implicit method, namely, intentional binding effect paradigm. Experiment 1a found that an activated cultural group identity enhanced the sense of agency. Next, Experiment 1b replicated the findings by recruiting a different ethnic group in the same society. Experiment 2 explored what may affect the intensity of induced sense of agency and found that perceived representativeness of the presented cultural stimuli was positively correlated with the intensity of induced sense of agency. Finally, Experiment 3 explored whether ethnic minority and majority groups would demonstrate different intensity of agency when their cultural identity was activated. The results showed that the sense of agency induced by the mainstream cultural stimuli was greater than that induced by the foreign cultural photographs. These patterns were not different between the two ethnic groups. Taken together, these findings reflected the dynamic nature of cultural identity construction in a multicultural society.